KEBIJAKAN RELOKASI PEDAGANG KAKI LIMA DI KOTA MANADO PROVINSI SULAWESI UTARA - Arnold Bura (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2018)
ABSTRACT The purpose of this study was (1) to analyze and find out what the Government’s policy to relocate street vendors Manado City in the center of the city of Manado. (2). To analyze and determine the factors that influence Relocation Policy Implementation street vendors by the City of Manado. Data collection techniques include in-depth interviews and documentation. Data analysis techniques include data reduction, data presentation and conclusion. Data validity checking techniques include degree of confidence, and the degree of dependency and certainty. In this study it was found that PKL relocation policy based Perwako No. 1 of 2006 concerning the relocation of street vendors in the market due to Manado Bersehati population and the presence of street vendors in the city center of Manado 45 raises complex issues that directly impact the other activities in the region, especially public transportation routes to be disrupted due to the capacity of the central area of the city of Manado 45 can no longer accommodate diverse activities. Assertiveness factor is needed in the City Government made a policy on street vendors. Are also important factors to be considered is the feasibility of a sale is seen from all aspects, primarily the physical condition of the building is also provided for the relocation of economic value that can be obtained by street vendors in these locations. Also affecting the relocation policy implementation is weak supervision and monitoring of the implementation of the policy. Thus it can be suggested that the relocation of street vendors Policy mayor Regulation No. 1 of 2006 should be revised or updated to a higher legal force the relocation of local regulation of street vendors. Government policy has had to consider the interests of both parties. On the one hand giving opportunity to all people to a decent life with his work, but still managing urban obliged to be a comfortable place for all activities of the citizens. Assertiveness factor is needed in the City Government made a policy on street vendors. This shows about government authority as the holder of the authority under applicable laws. Are also important factors to be considered is the feasibility of a sale, arranged from all aspects, primarily the physical condition of the building is also provided for the relocation of economic value that can be obtained by street vendors in these locations. Keywords: public policy, relocation, street vendors.